2003
DOI: 10.1046/j.1365-2907.2003.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of wild boar Sus scrofa in Western Europe, with particular reference to consumption of agricultural crops

Abstract: 1. The diet of wild boar Sus scrofa in Western Europe is reviewed, paying particular attention to the consumption of agricultural crops and the implications of this from the point of view of crop damage. Data were taken mainly from 11 studies that provide quantitative information about the consumption of different food types, but we also list all the foods reported as being eaten by wild boar in a total of 21 studies. 2. Vegetable foods occurred more frequently in the diet than animal foods, and also constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
396
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(416 citation statements)
references
References 39 publications
11
396
0
9
Order By: Relevance
“…The diet of wild boars in mountain ecosystems is not well studied, but the evidence suggests a clear relationship between rooting activity and the foraging for nutrient-rich foods such as animal proteins and plant storage structures (Baubet et al 1997;Schley and Roper 2003). Two of the local effects of grazing can explain the differences in wild boar rooting activities among stocking types and rates: faecal droppings differ between sheep and cattle because cattle produce larger scats and sheep disperse smaller pellets widely and in smaller quantities (Aldezabal et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The diet of wild boars in mountain ecosystems is not well studied, but the evidence suggests a clear relationship between rooting activity and the foraging for nutrient-rich foods such as animal proteins and plant storage structures (Baubet et al 1997;Schley and Roper 2003). Two of the local effects of grazing can explain the differences in wild boar rooting activities among stocking types and rates: faecal droppings differ between sheep and cattle because cattle produce larger scats and sheep disperse smaller pellets widely and in smaller quantities (Aldezabal et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Wild boars and feral pigs forage in large home ranges in which they can exploit an enormous variety of food sources (Gundlach 1986;Schley and Roper 2003). Under such conditions, individuals would beneWt from good spatial memory skills and a high Xexibility in behaviour (Held et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that a significant proportion (61-96%) of a feral pig's diet consists of organic plant material (Schley and Roper, 2003). Most notably, Gimenez-Anaya et al (2008) demonstrated that 33% of pig diet in Spain was underground roots and rhizomes.…”
Section: Discussionmentioning
confidence: 99%